UNIT 7.23 Using XHMM Software to Detect Copy Number Variation in Whole‐Exome Sequencing Data. (24th April 2014) - Fromer, Menachem; Purcell, Shaun M.
Abstract: Copy number variation (CNV) has emerged as an important genetic component in human diseases, which are increasingly being studied for large numbers of samples by sequencing the coding regions of the genome, i.e., exome sequencing. Nonetheless, detecting this variation from such targeted sequencing data is a difficult task, involving sorting out signal from noise, for which we have recently developed a set of statistical and computational tools called XHMM. In this unit, we give detailed instructions on how to run XHMM and how to use the resulting CNV calls in biological analyses. Curr. Protoc. Hum. Genet . 81:7.23.1‐7.23.21. © 2014 by John Wiley & Sons, Inc.